THE SYNCRETISM OF PRIMEVAL FIGURATIVE AND VERBAL REPRESENTATIONS (THE ORIGIN OF THE EMBLEMATIC FORMS) - Soletskyy, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The primeval patterns, visual and verbal designation structures have been considered in the paper. There is an attempt conducted to determine the specific sign structure expression of the primeval experience on the bases of the mythological consciousness studies, the linguistic world picture formation, while also taking into account the factors that influenced on the rise and development of folklore. This sign structure expression of the primeval experience laid bases for the creation of the emblematic forms in literature.